PENERAPAN METODE SIMPLE ADDITIVE WEGHTHING (SAW) DALAM EVALUASI KUALITAS RENDANG BERDASARKAN KRITERIA PRODUK DAN KEPUASAN KONSUMEN - Silvilestari, Silvilestari; Widya Perdana, Rika (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2026)
The increasing variety of rendang products available in the market has created challenges for consumers in identifying products with the best quality. Product evaluation cannot be based on a single aspect, as rendang quality is influenced by multiple criteria, including taste, aroma, color, spice composition, shelf life, price, and consumer satisfaction. The involvement of numerous assessment criteria often leads to subjective and inconsistent judgments. This study aims to develop a Decision Support System (DSS) for evaluating rendang quality and identifying the most suitable product based on measurable criteria. The method applied in this research is Simple Additive Weighting (SAW), selected for its capability to process multi-criteria decision-making through weighted evaluation. Data were collected from observations and respondent assessments of several rendang alternatives, followed by normalization and weighted calculations to determine preference values. The findings demonstrate that the SAW method can generate an objective and systematic ranking of rendang products. The highest preference score was obtained by alternative XIII with a value of 0.97, while the lowest score was recorded by alternative IV with 0.56. These results indicate that the proposed method is effective in distinguishing product quality based on the established evaluation criteria.